Penggunaan Tabung Penangkap Emisi Model Filter Ganda untuk Menurunkan CO Kendaraan Bermotor 4 Langkah - Damas Nurisa Aji; Siti Hani Istiqomah; Y.B Kamat Kartono (Sanitasi: Jurnal Kesehatan Lingkungan, 2008)
Motorcycle and car derived from technology development, apart from their ad-vantages as transportation vehicles are contributing to emit pollution gases such as carbon monoxide (CO) to environment. Another source for CO emis-sion is repair shop. In order to decrease CO pollution from that place, this e-mission catchment tube with double filter was developed. The tool consists of activated carbon and glass wool as the adsorbent filter agents. The study used a 100 cc 4-strokes motorcycle as the source of CO emission and auto check 974/5 for measuring the CO concentration. Both descriptively and analytically, the results showed that the tube was able to decrease the pollutant concentra-tion (p value 0,016). Howeer, it is suggested that any follow-up studies should explore the other possible material of the adsorbent, as well as the effective saturation time and the effective amount or number of the the filter.